2016
DOI: 10.1038/npp.2016.92
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Alcohol Increases Offspring Vulnerability to Stress

Abstract: The effect of preconception drinking by the mother on the life-long health outcomes of her children is not known, and therefore, in this study using an animal model, we determined the impact of preconception alcohol drinking of the mother on offspring stress response during adulthood. In our preconception alcohol exposure model, adult female rats were fed with 6.7% alcohol in their diet for 4 weeks, went without alcohol for 3 weeks and were bred to generate male and female offspring. Preconception alcohol-expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Now, several studies indicate a unique relationship between alcohol and stress stretching across generations. For instance, alcohol exposure paradigms such as parental adolescent injections (Przybycien‐Szymanska et al., ), maternal preconception gavage (Jabbar et al., ), and paternal exposure during prenatal development (Govorko et al., ) were found to alter hypothalamic–pituitary–adrenal (HPA) axis function in offspring. These studies are notable in light of the extensive literature showing that a family history of alcoholism is associated with impaired HPA axis function (Stephens and Wand, ).…”
Section: Cross‐generational Relationship Between Alcohol and Stressmentioning
confidence: 99%
“…Now, several studies indicate a unique relationship between alcohol and stress stretching across generations. For instance, alcohol exposure paradigms such as parental adolescent injections (Przybycien‐Szymanska et al., ), maternal preconception gavage (Jabbar et al., ), and paternal exposure during prenatal development (Govorko et al., ) were found to alter hypothalamic–pituitary–adrenal (HPA) axis function in offspring. These studies are notable in light of the extensive literature showing that a family history of alcoholism is associated with impaired HPA axis function (Stephens and Wand, ).…”
Section: Cross‐generational Relationship Between Alcohol and Stressmentioning
confidence: 99%
“…While these studies examined the effects of paternal preconception alcohol exposure on offspring, studies in our lab have recently shown that maternal preconception exposure also negatively affects offspring health, leading to an increase in adult offspring vulnerability to stress (Jabbar et al, 2016). Specifically, maternal alcohol exposure 3 weeks prior to conception results in several defects in adult F1 offspring, including increased hormonal stress response to an immune stressor, increased hypothalamic corticotropin-releasing hormone, decreased hypothalamic β-endorphin, and altered methylation status on CpG islands in stress regulatory genes in various brain areas.…”
Section: Evidence For Epigenetic Inheritance Of Alcohol-related Pamentioning
confidence: 99%
“…These deficits are rescued by administration of D-serine in the hippocampus, suggesting that the effects of the drug are reversible and have not damaged neuronal circuits permanently [19]. Further, alcohol exposure for 4 weeks in female rats before conception causes an exaggerated stress hormone response after an immune challenge in their offspring and dysregulates the expression of several stress-related genes in various brain regions [20]. Exposure of males to long-term intermittent ethanol vapor before conception decreases preference to ethanol in their offspring and increases their sensitivity to the anxiolytic effects of ethanol, which correlates with higher expression of brain-derived neurotropic factor (BDNF) in the ventral tegmental area (VTA) [21].…”
Section: Inter-and Transgenerational Epigenetic Inheritance Of Negatimentioning
confidence: 99%